Rancang Bangun Sistem Proteksi Pada Lightning Protection Device Berbasis Internet of Things - Rizka Adelia; Lela Nurpulaela; Ibrahim Ibrahim (Peneliti.net, 2022)
In the design of the electrical system, there are many parameters that need to be studied, one of which is the protection system because protection is very important for the electrical system.Protection is used as a guard for the continuity of electricity distribution and securing electrical equipment and loads connected to current and voltage due to a short circuit or disturbance and reducing the impac of damage that may arise so that the risk of fire is minimized. Good coordination of protection in the electrical system can increase the reliability of the system and maintain continuity of supply systems and systems that are integrated with the internet of things can facilitate fast, real time and reach information from a distance that is not to be an important thing, where checking the state of the supply of the electric power system is more controlled where a lightning strike is detected on the lightning protection device. In the design of a lightning protection device based on the internet of things, it consists of a 25 ampere NH Fuse, Omron MK2P PF083 8 Pin Relay, Schneider miniature circuit breaker, local miniature circuit breaker, earth leakage circuit breaker and Apps that are integrated with the internet. In the event of a short circuit or disturbance, the built-in protection system will cut off the affected channel.